Probability of mergers and acquisitions deal failure - Tanna, Sailesh; Yousef, Ibrahim; Nnadi, Matthias (Emerald, 2020)
Purpose The purpose of this paper is to investigate whether the probability of deal success/failure in mergers and acquisitions (M&As) transactions is influenced by a range of deal, firm and country-specific characteristics which tend to affect acquirers’ shareholder returns. The specific hypotheses under investigation relate to the method of payment (cash versus stock), target status (listed versus non-listed), diversification (domestic versus cross-border and industry-wide) and acquirers’ prior bidding experience. Additionally, the authors also investigate whether announced deals reflect an expectation about likelihood of deal completion. Design/methodology/approach The authors analyse the probability of deal success/failure in M&As by combining event study and probit regression-based methods. The authors use the standard event study methodology to calculate acquirers’ abnormal returns for up to 10 days before and after the announcement date. In the probit model, the dependent variable is the probability of deal i being failure depending on four sets of explanatory variables: method of payment, target status, diversification and acquirer bidding experience, along with a set of control variables. Findings The findings from event study confirm that market reaction is indifferent to whether announced deals are likely to be successfully completed or not, consistent with the efficient markets hypothesis. However, the results from cross-sectional, cross-country regressions confirm that the aforementioned deal characteristics, as well as certain firm and country level attributes do influence the likelihood of whether an announced deal is subsequently completed or terminated. Originality/value In examining whether the specific characteristics affecting the likelihood that M&A transactions, once announced, will ultimately succeed or fail, it seems natural to ask whether the market reaction at the time of deal announcement reflects an expectation regarding deal completion. This could be associated with specific deal or firm-level characteristics influencing shareholder returns or risk, and represents a unique contribution of this study, over and above the use of a global sample of M&A data. The empirical analysis investigates these issues by using an extensive, global sample of 46,758 M&A transactions from 180 countries and 80 industries, which took place between the years 1977 and 2012
Keywords: Mergers and acquisitions; Probit regressions; Abnormal returns; Event study